Collaborative Governance in Preventing Corruption in Public Goods and Services Procurement in Ngawi Regency - Reni Sulistyawati; Lulus Udjiwati; Khoyrul Anwar (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The commitment of the Ngawi Regency Government to preventing corruption in public procurement can be observed through the implementation of the collaborative governance concept. This study aims to analyze how collaborative governance practices are implemented in preventing corruption in the procurement of goods and services in Ngawi Regency, as well as to identify the factors that support and hinder the effectiveness of such collaboration. The research data were collected through observations and in-depth interviews, as well as documentation review of relevant literature and previous studies. The informants in this study included officials responsible for public procurement within the Ngawi Regency Government, the Ngawi Resort Police, the Ngawi District Attorney’s Office, and representatives of non-governmental organizations. Data analysis employed an interactive approach that emphasizes the cyclical, simultaneous, and iterative nature of the analytical process, which begins at the initial stage of data collection and continues through to the drawing of conclusions. Overall, the findings indicate that collaborative governance practices in preventing corruption in the procurement of goods and services in Ngawi Regency have shown a positive direction; however, further strengthening is still required in terms of the substantive aspects of collaboration. Existing collaboration tends to be more prominent in the form of administrative coordination among government institutions, while the involvement of the private sector and civil society remains limited. This condition suggests that collaborative governance has not yet been fully understood as a process of shared decision-making and joint oversight, but is still perceived primarily as a form of formal institutional cooperation.